Importance of protein flexibility in ranking inhibitor affinities: modeling the binding mechanisms of piperidine carboxamides as Type I1/2 ALK inhibitors1. Issue 8 (28th February 2015) - Kong, Xiaotian; Pan, Peichen; Li, Dan; Tian, Sheng; Li, Youyong; Hou, Tingjun
<x xml:space="preserve">Abstract</x> Anaplastic lymphoma kinase (ALK) has gained increased attention as an attractive therapeutic target for the treatment of various cancers, especially non-small-cell lung cancer (NSCLC).